Assessment of physico-chemical and bacteriological properties of Lake Lanao near Agus-1 Hydroelectric Power Plant in Marawi City, Philippines - Motalib, Jalaloden Mamaganding (Journal of Multidisciplinary Research Advancements, 2023)
This study assessed the physicochemical and bacteriological properties of Lake Lanao near the Agus-1 Hydroelectric Power Plant in Marawi City, Philippines. Water samples were collected from three locations in the vicinity of the power plant, and their pH, color, TDS, nitrate, turbidity, heterotrophic plate count, total coliforms, and thermotolerant coliforms were measured. The results showed significant variations in both physicochemical and bacteriological parameters among the water samples. The water sample taken 500 meters from the power plant had the highest pH, turbidity, and nitrate values, while the sample taken 1 kilometer away had the lowest values for these parameters. The sample taken 200 meters away had the highest heterotrophic plate count and total coliforms, while the sample taken 1 kilometer away had the highest thermotolerant coliforms. These results suggest that the Agus-1 Hydroelectric Power Plant has contributed to the deterioration of water quality in Lake Lanao. Therefore, this study underscores the need for regular monitoring and assessment of water quality near industrial sites to identify potential environmental impacts and implement necessary interventions to protect public health and the environment. The results can inform the development of policies and regulations related to water quality management in the Philippines. The study contributes to the growing body of knowledge on the water quality of Lake Lanao, highlighting the need to address gaps in research to better understand the complex interactions between the lake's physical, chemical, and bacteriological characteristics and the surrounding environment.